Effects of Dietary Anise (Pimpinella anisum L.) Oil on Growth Performance, Blood Parameters and Muscle Nutrient Content of Nile Tilapia (Oreochromis niloticus) - Serkan Tok; Mustafa ÖZ; Suat Dikel (Veterinary Medicine and Science)
ABSTRACT Objectives This study aimed to investigate the effects of dietary Pimpinella anisum (anise) oil supplementation on growth performance, haematological and biochemical parameters, antioxidant enzyme activities and tissue histopathology in Nile tilapia (Oreochromis niloticus). The goal was to determine the optimal inclusion level that promotes health benefits without inducing toxicity. Methodology A total of 240 juvenile Nile tilapia were randomly distributed into four groups: control (0.00%) and three treatments receiving anise oil at 0.10%, 0.20% and 0.30% for 8 weeks. Growth performance (weight gain, feed conversion ratio), haematological (RBC, Hb, WBC) and biochemical parameters (ALT, AST, glucose, lipids), oxidative stress markers (SOD, CAT, GPx) and histopathological changes in gill, liver, kidney and muscle tissues were evaluated. Results Anise oil supplementation at 0.10% and 0.20% significantly improved growth performance, haematological indices and antioxidant enzyme activities (p < 0.05) compared to the control group. However, fish fed 0.30% anise oil showed elevated liver enzymes, glucose and lipid levels, along with moderate tissue damage, indicating potential adverse effects at higher doses. Conclusions Dietary inclusion of 0.10% to 0.20% anise oil enhances the growth, physiological health and antioxidant defence in Nile tilapia. Nevertheless, 0.30% inclusion may impair metabolic balance and tissue integrity. Anise oil represents a promising natural feed additive for sustainable aquaculture when used at optimal levels.